2015
DOI: 10.2135/cropsci2014.09.0671
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Unique Genetic Sources of Soybean Rust Resistance from the USDA Soybean Germplasm Collection

Abstract: Soybean [Glycine max (L.) Merr.] rust is caused by the fungal pathogen Phakopsora pachyrhizi. Six rust resistance loci (Rpp1, 2, 3, 4, 5, and 6) have been reported. Crosses were made between 75 resistant plant introductions (PIs) and a susceptible elite line or cultivar. Bulked segregant analysis (BSA) was used to determine if the PI resistance genes mapped to a previously identified locus or to an unreported locus. Fifty‐two PIs had resistance genes that mapped to the Rpp3 region on chromosome 6 of the soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
(97 reference statements)
0
32
0
Order By: Relevance
“…Furthermore, another technique, the latest next-generation sequencing platforms, has improved the capacity to assess genetic variability at the genomic level in soybean accessions. It revealed important polymorphisms and haplotypes among individuals that responded differently to different isolates of the pathogen, improving the capacity of marker selection based on single polymorphism nucleotides (Kim et al, 2012;Harris et al, 2015;Yu et al, 2015).…”
Section: Genetic Resistancementioning
confidence: 99%
“…Furthermore, another technique, the latest next-generation sequencing platforms, has improved the capacity to assess genetic variability at the genomic level in soybean accessions. It revealed important polymorphisms and haplotypes among individuals that responded differently to different isolates of the pathogen, improving the capacity of marker selection based on single polymorphism nucleotides (Kim et al, 2012;Harris et al, 2015;Yu et al, 2015).…”
Section: Genetic Resistancementioning
confidence: 99%
“…pachyrhizi population. Thus, further investigation is needed to determine whether the SBR resistance of DT 2000 is controlled by the same genes/alleles as those previously reported [13,17,18,47,53]. Moreover, it is worth noting that a number of the USDA germplasm accessions that have shown resistance to P .…”
Section: Discussionmentioning
confidence: 85%
“…An Rpp gene associated with lesion type was mapped to the genomic location of the Rpp3 locus [47], but it is not yet known whether DT 2000 carries the same allele as PI 462312, the source of the original Rpp3 gene. Other studies have shown that numerous SBR-resistant soybean germplasm accessions carry a resistance gene at the Rpp3 locus [13,17,18,47]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Hyuuga) (chr 6; PI 506764) was initially believed to be a novel allele at the Rpp3 locus (Monteros et al, 2007); however, a subsequent study showed that PI 506764 actually has a natural pyramid of genes at the Rpp3 and Rpp5 loci (Kendrick et al, 2011). Additionally, many other resistance sources have been documented representing what appears to be many different plant introductions with resistance genes at the same loci, or novel resistance alleles (Harris et al, 2015).…”
Section: Soybean Rust Resistance Genes Original Sources and Reactiomentioning
confidence: 99%